AN AUDIT OF SINGLE STAGE HYPOSPADIAS REPAIR AT AYUB HOSPITAL COMPLEX, ABBOTTABAD - Khattak, Irfan U.; Akbar, Mohammad; Nawaz, Mohammad; Saleh, Ali Al-; Noor, Bakhmal; Rehman, Zia -ur- (Journal of Ayub Medical College Abbottabad, 2004)
Background: Single-stage hypospadias repair is increasingly being performed. We report our experience at a general surgical unit. Methods: The first one hundred repairs are included in this observational study, set up to evaluate our results. Hypospadias was graded as distal, penile shaft or peno-scrotal, with or without chordee. A single stage procedure of urethral plate elevation, excision of fibrous tissue with preputial onlay flap was used in all patients. Results: First 100 operated patients are included in this study. Frequency of major complications was 33%, including fistula (17%), meatal stenosis (7%), premature tube dislodgment (3%), epidermal sloughing and persistent chordee (2% each), and retained tube and torsion penis (1% each). Fistula rate was high (17%). Success in fistula repair was low (53%). In five patients (5%) the urethral plate was transected as it was too short and fibrosed. Conclusions: Patients presented early. This procedure may successfully relieve chordee except in peno-scrotal cases. Fistula is a common complication. Early fistula repair may improve outcome. One fourth of the children had a poor cosmetic result. It was not a major concern for parents. Key words: single stage, Hypospadias repair, complications, cosmesis